Convergence of Faith and Capital: Analysis of the Implementation of Sharia-Based Financial Institutions in Indonesia - Putra Anshari Siregar; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this study is to analyze whether religious and commercial factors can affect Islamic-based finance in Indonesia. As well as with a lack of knowledge about faith and a lack of adequate finances, can Islamic finance affect profit. In this analysis, the researcher used the library research method. Therefore, the source of the research data was obtained from the literature/library in the form of books or books, notes, journals, research reports from previous researchers and other related references. with the subject matter to incorporate the principles of Islamic economics in completing research.